One, Mad Hornpipe: Dance as a Tool of Subversion in Brian Friel’s Molly Sweeney - Ojrzyńska, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2011)
The plot of Brian Friel's Molly Sweeney oscillates around the theme of perception, blindness and eye-sight recovery. Although visually impaired, the eponymous character is a self-reliant and independent person who is very active, both professionally and socially. What serves as the source of tragedy in the play is the male desire to compensate for Molly's physical disability perceived as a sign of deficiency and oddity that needs to be normalized. Prompted by her husband, Molly decides to undergo a surgery which gives her a chance to regain sight and, thus, become a part of the world of the visually abled. Yet, subsequent to the operation, Molly cannot adapt herself to the new reality and develops a medical condition called blindsight, which leads to her final alienation and confusion. Focusing predominantly on the main character of the play, this paper examines the ways in which Molly Sweeney experiences the surrounding world and seeks satisfaction and self-fulfilment through physical activities, such as swimming or dancing, which she vividly describes in her monologues. It explores the double nature of Molly who, despite her self-sufficiency, capacity for rebellion and a sense of autonomy, seems prone to male manipulation exercised at first by her father, later by her husband Frank and doctor Rice. Her expression of independence becomes particularly conspicuous in the scene of a party organized the night before her surgery when she performs a wild and frantic hornpipe, which serves as a form of momentary upheaval and a visualization of the outburst of extreme emotions. Although the dance is not presented onstage, it has a crucial function in the play, for it serves as its powerful climax, after which Molly experiences gradual deterioration. Interpreted in the context of the history of Irish dance, the mad hornpipe appears replete with meanings and allusions. Traditionally associated with human sexuality and the female element, dance was often treated by the Irish clergy with a great deal of distrust as a source of evil and moral corruption. Consequently, like in the case of the frenzied reel in another famous Frielian play, Dancing at Lughnasa, the limitless and unrestricted performance in the climactic scene of Molly Sweeney may be seen as a tool of subversion and female opposition to the Irish patriarchal order. It is a unique moment in which the protagonist seizes male power and gains full, though very temporary, control over her life.